Gry intertekstualne Stephena Kinga - "Baśniowa opowieść" wobec popkultury, klasyki i mitu = Stephen King`s intertextual games - "Fairy Tale" and pop culture, classics and myths - Wawryk, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Published in 2022, "Fairy Tale" by Stephen King contains a number of references to classic and contemporary texts. In this fantasy novel, intertextuality is an expression of a conscious creative strategy. The novel follows the determinants of postmodern literature, and it can be interpreted in mythocritical and psychoanalytical terms. The realistic, fairy-tale/magic and mythical themes were analysed in the article.
Keywords: King, Stephen (1947- ). Baśniowa opowieść; fantasy; interteksualność; baśń; klasyka literacka; popkultura; mit; intertextuality; fairy tale; literary classics; pop culture; myth